The potential of SARS-CoV-2 antigen-detection tests in the screening of asymptomatic persons. (November 2021) - Wachinger, Jonas; Olaru, Ioana Diana; Horner, Susanne; Schnitzler, Paul; Heeg, Klaus; Denkinger, Claudia M.
Abstract: Objectives: The aim was to assess the performance of antigen-based rapid diagnostic tests (Ag-RDTs) for SARS CoV-2 when implemented for large-scale universal screening of asymptomatic individuals. Methods: This study was a pragmatic implementation study for universal Ag-RDT-based screening at a tertiary care hospital in Germany where patients presenting for elective procedures and selected personnel without symptoms suggestive of SARS-CoV-2 were screened with an Ag-RDT since October 2020. Test performance was calculated on an individual patient level. Results: In total, 49 542 RDTs were performed in 27 421 asymptomatic individuals over a duration of 5 and a half months. Out of 222 positive results, 196 underwent in-house confirmatory testing with PCR, out of which 170 were confirmed positive, indicating a positive predictive value of 86.7% (95% CI 81.2–91.1%). Negative Ag-RDTs were not routinely tested with PCR, but a total of 94 cases of false negative Ag-RDTs were detected due to PCR tests being performed within the following 5 days with a median cycle threshold value of 33 (IQR 29–35). Discussion: This study provides evidence that Ag-RDTs can have a high diagnostic yield for transmission relevant infections with limited false positives when utilized at the point of care on asymptomatic patients and thus can be a suitable public health test for universal screening.